Pemanfaatan Surat Keterangan Asal Indonesia Dalam Peningkatan Investasi Berorientasi Ekspor Australia Ke Indonesia - Victor Tulus Pangapoi Sidabutar (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
Indonesia has signed a trade agreement with Australia and hoped that this agreement can benefit both parties to face global free trade. Indonesia is not Australia's main trading partner and Indonesia's exports to Australia tend to decline but Indonesia can take advantage of the Australian export market which has trade agreements with Indonesia to indirectly increase Indonesian exports by utilizing Indonesia’s Certificate of Origin (CoO) as a partner for Australian export product producers by using Third Country Invoicing and back-to-back preferential CoO